Effectiveness of katuk leaf chlorophyll (Sauropus androgynus (L) Merr) with blue and red laser a ctivation to reduce Aggregatibacter actinomycetemcomitans and Enterococcus faecalis biofilm - P. A. D. Permatasari; S. D. Astuti; A. K. Yaqubi; E. A. W. Paisei; . Pujiyanto; Nasrul Anuar (Biomedical Photonics, 2023)
In this study, the efficacy of using Sauropus androgynus (L) Merr, a katuk leaf chlorophyll photosensitizer, to reduce Aggregatibacter actinomycetemcomitans and Enterococcus faecalis biofilm was investigated. A red and blue diode laser is used as the light source. The sample was split into four groups: a negative control group, a positive control group, a blue laser treatment group (B), and a red laser treatment group (R), both with and without the addition of katuk leaf chlorophyll 1.6 mg/ml, and with varying densities of laser energy exposure of 2.5 J/cm2, 5 J/cm2, 7.5 J/cm2, and 10 J/cm2. Laser exposure and chlorophyll photosensitizer were tested using ELISA and ANOVA. At an energy density of 10 J/cm2, the optimal bacterial mortality rate was obtained in each treatment group. Namely, in the Aggregatibacter actinomycetemcomitans biofilm, the negative group, the number of deaths was 73.30% using a blue diode laser and 63.25% using a red diode laser. In the positive group, the number of deaths was 86.12% using a blue diode laser and 83.29% using a red diode laser. In the Enterococcus faecalis biofilm, in the negative group, the number of deaths was 67.78% using the blue diode laser and 75.33% using the red diode laser, and in the positive group, the number of deaths was 71.71% using the blue diode laser and 86.41 using a red diode laser. Exposure to blue and red diode lasers activates chlorophyll in katuk leaves, killing bacteria and reducing biofilms.